Effect of Selenium on Thyroid Disorders: Scientometric Analysis - Farzad PAKDEL; Roghayeh GHAZAVI; Roghayeh HEIDARY; Athena NEZAMABADI; Maryam PARVIZI; Mahsa HAJI SAFAR ALI MEMAR; Reza GHAREBAGHI; Fatemeh HEIDARY (Tehran University of Medical Sciences, 2019)
Background: Association of Selenium (Se) deficiency, an essential trace element, has been found with human diseases. Identifying literature trends on the effects of Se on the thyroid may guide in planning future studies. Methods: A literature search was conducted using the Web of Science database to identify studies on Se and the thyroid published over the 20 years duration (1995-Dec 2014). Scientometric indices were used to draw field maps. The scientific processes, structure, evidence history, and international collaborations were included in the map. The most influential authors, journals, institutions, and countries were also examined. Results: Our search identified 184 research and review papers. The number of scientific studies on Se and the thyroid has been irregular, but interest in this topic has increased in recent years. The highest number of studies was published in 2014 (16 papers) and overall growth factor of publication was 3.78. Overall, 744 authors from 282 institutions in 43 countries published in this field. The author J. Kohrle (828 citations, 14 publications), and German scientists (1272 citations, 30 publications) were most influential. Conclusion: This study reveals the interrelationships between different publications on the effects of Se on the thyroid. Leading scientific issues and their extent of impact were successfully determined by examining citations. The results of systematic citations and mapping fields can be used to assist in policy and management contexts.